Stochastic self‐scheduling of generation companies in day‐ahead multi‐auction electricity markets considering uncertainty of units and electricity market prices. Issue 7 (1st July 2013) - Vatani, Behdad; Amjady, Nima; Zareipour, Hamidreza
Abstract : This study presents a new stochastic self‐scheduling model for generation companies (GENCOs) in day‐ahead electricity markets including energy and reserves auctions. The proposed stochastic model takes into account both the uncertainty of predicted market prices and forced outages of generating units. Also, financial risk of GENCOs is formulated through well‐known conditional value‐at‐risk index. The proposed self‐scheduling model is tested on the IEEE 118‐bus test system and the obtained results are discussed.